Insights into Pollinator Health and Sustainable Agriculture Inferences from Melissopalynological Investigation - Sneh Trivedi; Alka Srivastava (The Bioscan, 2025)
Melissopalynology, the analysis of pollen in honey, serves as a critical tool for understanding honeybee foraging dynamics and the botanical composition of honey across different ecological contexts. The present study investigates the seasonal variation in pollen composition of honey samples collected from eight agricultural landscapes in Kanpur and Unnao districts, Uttar Pradesh, India, encompassing areas viz. Rooma, Narwal, Shuklaganj, Dalhan, Barui, Asadhna, Saraiya, and Sarsaul. Pollen analysis was conducted using the Erdtman (1953) acetolysis method to detect pollen contents in honey samples. Results indicate a distinct temporal shift in pollen composition, with winter honey predominantly containing Brassica campestris, Solanaceae, Coriandrum sativum, and Bombax ceiba, signifying the critical role of Brassica sp. as a primary nectar source, to summer honey exhibiting dominance of Syzygium sp., Helianthus sp., Anacardiaceae, Poaceae, and Asteroideae, reflecting seasonal adaptation in honeybee foraging behavior. The findings underscore the significance of melissopalynology in elucidating pollinator-plant interactions, informing sustainable agricultural practices, and promoting biodiversity conservation. Furthermore, the study highlights the potential of melissopalynological analysis for assessing the impact of agricultural inputs and optimizing land management strategies. Longitudinal monitoring of pollen spectra in honey can provide valuable insights into the dynamic relationship between agricultural practices, pollinator health, and ecosystem stability.